PEMBENTUKAN KOPERASI WUJUD KEPEDULIAN PENINGKATAN TARAF KEHIDUPAN PARA PETANI DI DESA LENGANSARI KECAMATAN SUKARAJA KABUPATEN SUKABUMI - Riswanto, Ari (JE (Journal of Empowerment), 2017)
The increasing of women capacity to survive is something that must always be fought. Lengansari village of Sukaraja District of Sukabumi is the representative of the struggling people who are always be the farm laborers on their own dwelling place. This phenomenon triggered the idea of the community service activities which is be an annual program of STKIP PGRI Sukabumi. Group III that is located in Lengansari village initiated to establish a cooperative as a form of education to increase the public standard of living of rural communities. In order to gain the villagersâ€™ expectation, the training was done conductively and systematically by a team under the lecturer guidance. This project was successfully gained because of the hard work of the students of group III totaling 25 students who were directed by the lecturer and in collaboration both with the related apparatus in the region and the department of cooperatives.Â